(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2020)
Antimicrobial and antitumor activities of resveratrol, a compound found mainly in grapes, have already been demonstrated. However, its low bioavailability is a limiting factor for therapeutic application. Polymeric micelles can be an approach to solve this problem since they can encapsulate hydrophobic substances. We developed and characterized micellar formulations containing resveratrol and evaluated their cytotoxic and antimicrobial effects. The formulations were prepared by the cold dispersion method with different concentrations of F127 (5 or 10% w/w) and resveratrol (500 or 5000 µM). The formulations were characterized according to size, polydispersity index, pH, encapsulation rate and in vitro release. Cytotoxic effect was evaluated on a bladder cancer cell line and antimicrobial effect was evaluated on E. coli, S. aureus and C. albicans. One of the formulations (10% w/w of F127 and 5000 µM of resveratrol) was a monodispersed solution with high encapsulation rate, thus it was chosen for the cytotoxicity and antimicrobial assays. MS10+RES-3 was able to preserve the antimicrobial and cytotoxic activity of resveratrol. This is the first study that evaluated antimicrobial potential and cytotoxicity of micelles containing resveratrol on bladder cancer cells and the results showed that micellar nanostructures could ensure the maintenance of the biological activity of resveratrol.